Political motivation as a key driver for universal health coverage - Venkateswaran, Sandhya; Slaria, Shruti; Mukherjee, Sampriti (Frontiers in Public Health, 2022)
Variation in public investments to health, health outcomes, and progress toward universal health coverage across countries is vast and neither economic status nor the knowledge on solutions have borne out to be binding constraints to health improvements. The drivers for universal health coverage go beyond the macro-economic context of a nation, and as pointed out by scholars, are deeply linked with the extent of political prioritization of healthcare. Low public investments to health in India and slow movement toward universal health coverage underline the need for more attention to the political priority accorded to health in the country. While the role of politics in policy reforms has been established by several scholars, this paper seeks to identify the intrinsic motivations or incentives that drive political priority. Drawing on the experience of nine countries, the paper attempts to inform the analysis for countries such as India (where progress toward universal health coverage remains slow), on the political incentives for prioritization of healthcare, and how these may be shaped or strengthened. The analysis finds that health care reforms happen in (at least) two stages: the existence and recognition of a national context and a problem, followed by political opportunities and motivations which lead political leaders to address the identified problem. The paper separates motivation as a distinct factor for analysis because, in the absence of strong incentives, not every political opportunity may lead to attention to an issue, and finds that reforms were motivated by a need to gain political legitimacy by an incoming regime, or by its political ideology, or a combination of both. Importantly, political motivation does not always take root in itself, but often driven by external factors and stakeholders who contribute to creating or strengthening incentives for political attention. A greater role from citizens and other actors such as elected representatives, questioning status quo and highlighting the schisms in the social contract between a political regime and citizens may contribute to shifting the source of legitimacy for leaders.